Fire and fury inside the Trump White House - Wolff, Michael (New York Henry Holt and Company, 2018)
With extraordinary access to the West Wing, Michael Wolff reveals what happened behind-the-scenes in the first nine months of the most controversial presidency of our time in Fire and Fury: Inside the Trump White House.
Includes index.
Keywords: Trump, Donald, 1946-